Administración y control de Inventario y su incidencia en los resultados de la Empresa de Productos Orgánicos Chimborazo SUMAK LIFE CÍA.LTDA., período 2014 - Valdiviezo Valdiviezo, María Belén (2016)
The research paper entitled "ADMINISTRATION AND INVENTORY CONTROL AND ITS IMPACT ON COMPANY RESULTS OF ORGANIC LIFE CHIMBORAZO SUMAK CIA. LTDA., PERIOD 2014 "was conducted in order to identify how they are managed and controlled inventories of raw materials, inputs and finished products and their relationship to management performance during the study period. Development work was required to make a diagnosis of the current situation of the company to proceed with the search for theoretical information on the study variables, the same as that obtained from books, textbooks, physical and virtual documents. The methodology used was deductive hypothetical because starting with an overview of the management and control of inventories hypothesis was established. The research was descriptive and historical because the characteristics of the variables are reported for a specific period. As for its design was documentary and field because he went to the company to see financial documents and procedures used. Regarding the population consisted of the manager, the accountant and employees who have responsibility for the winery. Interviews applied allowed to determine the views of employees the same as analyzed by comments made by the researcher. These results together with the analysis of the financial statement of the period provided guidelines for the drafting of conclusions and recommendations for the design of procedures instructive as a contribution to improving the management and control of inventories in the company